Rapid Preparation of Platinum Catalyst in Low-Temperature Molten Salt Using Microwave Method for Formic Acid Catalytic Oxidation Reaction - Haidong Zhao; Xiaoyan Hu; Hongbiao Ling; Ji Li; Weixu Wang; Jingtao Guo; Rui Liu; Chao Lv; Zhen Lu; Yong Guo (Molecules)
In this paper, platinum nanoparticles with a size of less than 50 nm were rapidly and successfully synthesized in low-temperature molten salt using a microwave method. The morphology and structure of the product were characterized by SEM, TEM, EDX, XRD, etc. The TEM and SEM results showed that the prepared product was a nanostructure with concave and uniform size. The EDX result indicated that the product was pure Pt, and the XRD pattern showed that the diffraction peaks of the product were consistent with the standard spectrum of platinum. The obtained Pt/C nanoparticles exhibited remarkable electrochemical performance in a formic acid catalytic oxidation reaction (FAOR), with a peak mass current density of 502.00 mA·mg−1Pt and primarily following the direct catalytic oxidation pathway. In addition, in the chronoamperometry test, after 24 h, the mass-specific activity value of the Pt concave NPs/C catalyst (10.91 mA·mg−1Pt) was approximately 4.5 times that of Pt/C (JM) (2.35 mA·mg−1Pt). The Pt/C NPs exhibited much higher formic acid catalytic activity and stability than commercial Pt/C. The microwave method can be extended to the preparation of platinum-based alloys as well as other catalysts.